Compensatory upregulation of respiratory chain complexes III and IV in isolated deficiency of ATP synthase due to TMEM70 mutation - Havlíčková Karbanová, Vendula; Cížková Vrbacká, Alena; Hejzlarová, Kateřina; Nůsková, Hana; Stránecký, Viktor; Potocká, Andrea; Kmoch, Stanislav; Houštěk, Josef (Biochimica et biophysica acta, 2012)
Early onset mitochondrial encephalo-cardiomyopathy due to isolated deficiency of ATP synthase is frequently caused by mutations in TMEM70 gene encoding enzyme-specific ancillary factor. Diminished ATP synthase results in low ATP production, elevated mitochondrial membrane potential and increased ROS production. To test whether the patient cells may react to metabolic disbalance by changes in oxidative phosphorylation system, we performed a quantitative analysis of respiratory chain complexes and intramitochondrial proteases involved in their turnover. SDS- and BN-PAGE Western blot analysis of fibroblasts from 10 patients with TMEM70 317-2A>G homozygous mutation showed a significant 82-89% decrease of ATP synthase and 50-162% increase of respiratory chain complex IV and 22-53% increase of complex III. The content of Lon protease, paraplegin and prohibitins 1 and 2 was not significantly changed. Whole genome expression profiling revealed a generalized upregulation of transcriptional activity, but did not show any consistent changes in mRNA levels of structural subunits, specific assembly factors of respiratory chain complexes, or in regulatory genes of mitochondrial biogenesis which would parallel the protein data. The mtDNA content in patient cells was also not changed. The results indicate involvement of posttranscriptional events in the adaptive regulation of mitochondrial biogenesis that allows for the compensatory increase of respiratory chain complexes III and IV in response to deficiency of ATP synthase.
Keywords: messenger RNA; membránové proteiny; Peptide Hydrolases; Up-Regulation; Gene Expression Profiling; Electron Transport; mitochondrie; Membrane Proteins; Electron Transport Complex IV; proteasy; Mitochondrial Proton-Translocating ATPases; upregulace; mitochondriální protonové ATPasy; mutace; oxidativní fosforylace; respirační komplex III; DNA, Mitochondrial; transport elektronů; Oxidative Phosphorylation; Mitochondrial Proteins; Mutation; RNA, Messenger; Humans; mitochondriální DNA; Fibroblasts; Mitochondria; stanovení celkové genové exprese; mitochondriální proteiny; respirační komplex IV; lidé; fibroblasty; Electron Transport Complex III